Spasial Autokorelasi Sebaran Demam Berdarah Dengue Di Kecamatan Ambarawa - Kartika Dian Pertiwi; Ita Puji Lestari (Universitas Ngudi Waluyo, 2020)
Incidence of Dengue Hemorrhagic Fever (DHF) in Ambarawa increased significantly during 20118-2019. In 2018 there were 19 DHF events, and in 2019 there were 124 DHF events. This study was conducted to determine the spatial distribution of dengue spread and environmental conditions associated with breeding grounds, resting places, installations, holes in walls, ceiling, temperature, humidity, air pressure, the use of mosquito nets in 2019.This research is a descriptive study with ecological studies. The population of this study was all DHF events in the working area of Ambarawa Health Center from 2018-2019 with the criteria to have a clear address with a total of 130 DHF events. This study uses secondary data containing DHF event data from Ambarawa Health Center and population data in the working area of Ambarawa Health Center in 2018-2019 and primary data related to the geographical location of DHF events. As a research instrument used is a questionnaire table, Environmental observation sheet, Global Positioning System (GPS), thermogygrometer. The results obtained from the pattern of the spread of DHF events in the working area of Ambarawa Health Center in 2018 were patterned spread with NNI 1.4 in 2018 and grouped (grouped) with NNI 0,000258 in 2019. The extent of the distribution of DHF events in Ambarawa was from in 2018-2019 the more widespread with the discovery of dengue patients in all kelurahan in 2019 after not found dengue patients in Baran and Bejalen villages in 2018. Dissemination of DHF information in Ambarawa from 2018-2019 can be found in Kupang District, spreading DHF patterned distribution (disbanded) in 2018 and in groups (in groups) in 2019 with the value of the NNI getting smaller.